Factors affecting cooperatives’ performance in relation to strategic planning, human capital and members’ participation / Mahazril ‘Aini Yaacob, Hafizah Hammad Ahmad Khan and Zuraini Yaacob - Yaacob, Mahazril ‘Aini; Hammad Ahmad Khan, Hafizah; Yaacob, Zuraini (Research Management Institute, 2012)
The cooperative society plays significant roles towards the economic development in Malaysia. It was first established in 1922 to protect the welfare of rural people and has expanded its establishment until today. With the aims to help its members, it is said that cooperative needs to accelerate its performance. However, there are issues regarding its weaknesses, especially in the management, financial and members’ participation. Result shows that human capital plays a vital role in influencing the cooperatives performance while strategic planning and members’ participation turns out to be insignificant. Result suggests that even though the cooperatives do not have a proper short term and long term planning, it would not affect their performances. This might be due to the nature of the board members who are at the age of 46 and above whereby these groups of people prefer to use traditional method in their management. Therefore, their active participation does not significantly influence the cooperatives performance. The findings conclude that the cooperatives should enhance its human capital development by developing a good training and education programmes as well as a good promotion scheme so as to boost up its performance towards realizing the National Cooperative Policy 2011-2020.